The Informed Consent in the medical practice. Differences between theory and practice. Clinical experience in the Republic of Argentina - Marini, Julio César (Medicina e Morale, 2021)
What happens with the informed consent is not limited to a medical specialty only, and the perception of an important gap between its theory and practice exists in all the medical practice that requires it. We consider the informed consent as a continuous process grounded in the physician-patient relationship, and the gap between theory and practice could be diminished when that relationship improves. As bioethicists we consider the physician-patient relationship as a vivid space because it is the consequence from the interaction between two free and responsible persons. It is vivid because it involves feelings, emotions, and passions, sometimes expressed, and/or restrained by reason and will, so that participants can reach the common good thus giving way to the consent.